2014
DOI: 10.15376/biores.9.4.5976-5987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-flocculation of Lime Mud CaCO3 Filler on AKD Sizing Efficiency

Abstract: Lime mud (LM), whose main component is calcium carbonate, is a byproduct in the pulp and papermaking industry. For non-wood pulping processes, large amounts of LM are produced every year, and a portion of them has been used as a paper filler. However, LM significantly lowers alkyl ketene dimer (AKD) sizing efficiency when added to paper. In this study, LM slurry was first pre-flocculated using some commonly used wet-end additives; then, the pre-flocculated LM was added to the pulp for handsheet preparation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The pulp fiber yield, compared to the used wood, amounts to 40–60% in the Kraft process, while the obtained pulp fibers are barely damaged. The Kraft process is an economical and energy‐saving process, as the extracted lignin can be burned immediately afterwards for the generation of required energy, and, the pulping chemicals can be retrieved and reused …”
Section: Design and Manufacturing Of Highly Filled Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulp fiber yield, compared to the used wood, amounts to 40–60% in the Kraft process, while the obtained pulp fibers are barely damaged. The Kraft process is an economical and energy‐saving process, as the extracted lignin can be burned immediately afterwards for the generation of required energy, and, the pulping chemicals can be retrieved and reused …”
Section: Design and Manufacturing Of Highly Filled Papersmentioning
confidence: 99%
“…Hydrophobic coatings help to make papers more waterproof which is the functional purpose of sizing agents. Therefore, precoating the filler particles and increasing the filler content can reduce the need for sizing agents . Besides improving the adherence of micrometer‐sized filler particles to the outside of pulp fibers by the precoating, filler nano‐particles can be pre‐mixed with pure pulp fibers during beating.…”
Section: Design and Manufacturing Of Highly Filled Papersmentioning
confidence: 99%
“…Therefore, it can be concluded that AKD might play an important role in the swelling properties or hornification of fiber. In recent years, many research results about the hydrophobic interaction of AKD on original fibers have been published [12,13]. In general, it is believed that AKD reacts with cellulose fiber and forms a β-keto ester bond, hence making paper hydrophobic [14].…”
Section: Introductionmentioning
confidence: 99%
“…ImE sludge is a kind of by-product in the alkali recovery from pulping process of paper industry [1,2]. the main component of lime sludge is calcium carbonate and it also contains a small amount of residual metal compounds and alkali.…”
mentioning
confidence: 99%
“…the results showed that both the paper water resistance and lime sludge retention were highly controlled by the added CPAM [11]. CPAM was used to preflocculate lime sludge and AKD, which was proved to be effective in improving the sizing efficiency [2]. In general, much effort has been devoted to the cPCC filling system.…”
mentioning
confidence: 99%